Public policies, open innovation ecosystems and innovation performance: Analysis of the impact of funding and regulations - Joana Costa; António Carrizo Moreira (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Open innovation (OI) has been implemented to develop competitive advantages based on the management of innovation with external players. As such, it is expected that the generalized adoption of OI practices needs to be nurtured by governmental public policies in order to enhance OI-based ecosystems. The role of open innovation ecosystems is known by the importance of multiple synergies among players/stakeholders, which are expected to be supported by regulations and funding to consolidate firms' innovation results. This paper analyzes the role of regulations and funding on firms' innovation performance using the double-hurdle estimation procedure. The results show that, in the first tier, inbound knowledge flows positively affect performance, and, in the second tier, public funds further reinforce innovation performance and fiscal and security regulations. In contrast, as regulations are perceived as barriers, they fail to impact innovation performance. With this paper, we manage to shed light on the importance of public policy funds in the support of thriving OI-based ecosystems as enhancers of firms' innovation performance.
Keywords: 650; CIS; Cragg’ s Tobit; double-hurdle model; funds; innovation performance; open innovation; regulations